ANALYSIS OF LEGAL PROTECTION FOR MEDICAL PERSONNEL IN MALPRACTICE CASES: AN INDONESIAN LEGAL PERSPECTIVE - Andreas Harry; Gunawan Widjaja (Jurnal Kesehatan, 2025)
This study examines the legal protection for medical personnel in the face of malpractice cases in Indonesia, focusing on the applicable regulations, dispute resolution mechanisms, and implementation challenges. Through analysis of the Medical Practice Act and the Health Act, it is found that these regulations provide a sufficient legal framework for the protection of medical personnel. Malpractice dispute resolution can be done through mediation and arbitration as an alternative to litigation, which is expected to be faster and fairer. However, there are challenges in the understanding and implementation of the regulations by medical personnel, as well as the need for increased education and socialisation on their legal rights. This study emphasises the important role of medical professional bodies in providing legal support to ensure effective protection and maintenance of quality medical services in Indonesia.